The hydrolase PbHAD32 participates in the adherence of Paracoccidioides brasiliensis conidia to epithelial lung cells (2012)
ABSTRACT: Adherence of the dimorphic pathogenic fungus Paracoccidioides brasiliensis to lung epithelial cells is considered an essential event for the establishment of infection. We have previously shown that the PbHAD32 hydrolase is important in this early stage of the host-P. brasiliensis yeast cells interaction. The aim of this study was to further elucidate the role of PbHAD32 in conidial thermodimorphism and their interaction with lung epithelial cells. Analysis of the PbHAD32 gene expression revealed higher mRNA levels during the conidia to mycelia (C – M) germination when compared to the conidia to yeast (C – Y) transition. Moreover, PbHAD32 was consistently expressed at higher levels upon infection of lung epithelial cells, but to a greater extent when conidia germinated to produce mycelia. Interestingly, at this particular transitional stage, more conidia adhered to epithelial cells than when they were transiting to the yeast form. Altogether our data further corroborates the importance of PbHAD32 during initial adherence to host cells and suggest that the 32-KDa hydrolase may also participate at different stages of the C – M and C – Y conversions.